For kids - Uma análise da dinâmica dos formatos de programas infantis da tv paga no Brasil - Ferreira, Kécia Garcia (2019)
This project has as a main goal to dialogue about genres, formats and themes of children´s programs that belong to the Brazilian pay TV programming in order to give bases to a proposal of formacts that are able to characterize these programs. It was developed a quantitative and qualitative reserach wich corpus was built based on cataloguing the programming and programs exhibited between 2017 and 2019, on the 15 Pay-TV channels, classified as "for kids" by ANCINE. The quantitative research had as source informations provided by the channels, programmers, development agencies, producers and coproducers, available on their official websites. After cataloging all children's programs, the profile of the channels was outlined, concerning target audience, country of origin and main theme, and then it was presented a first discussion about format categories for the programs, which were divided into format- exhibition, format-technique and format-intentionality. From the results presented, we believe it is possible to identify better the formats in children's programs, besides those generic labels "for kids" and "animation", or “comedy”, and even “diverse”, related to genres, currently given to the programs.